Design and In-vitro Evaluation of Gastro Retentive Bilayer Floating Tablets of Rosiglitazone Maleate - Patil, Shrishail Shital (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSRTACT In the present study, rosiglitazone maleate, a novel anti-diabetic agent, was formulated into Gastroretentive bilayer floating tablets and evaluated for various physico chemical properties. The immediate release layer was formulated using different super disintegrants and controlled release layer using Hydroxypropyl methylcellulose K100M (HPMC K100M) by direct compression method. Among various super disintegrants used, cross caramellose at the concentration of 8% was found sufficient to cause rapid drug release whereas 50% HPMC of the total weight of the tablet effectively controlled the drug release over a period of 24 h. Sodium bicarbonate at the concentration of 14 %w/w reduced the buoyancy lag time to less than 3 minute for the optimized tablet (F5). The total floating time for different formulations was in the range of 10-28 h. The concentration of HPMC has marked influence on the drug release from the prepared floating tablets. Release profiles indicated that, increasing the polymer concentration has drastically retarded the release of Rosiglitazone maleate. The optimized tablets F5 showed controlled and complete drug release over a period of 24 h. Tablets followed diffusion controlled first order kinetics. FT-IR and DSC studies revealed the absence of any chemical interaction between drug and polymer used. During the stability period optimized formulation was found to be stable with respect to physico-chemical and drug release characteristics.